AGN feedback in the nucleus of M 51 - Querejeta, Miguel; Bigiel, Frank (Astronomy and astrophysics, 2016)
AGN feedback is invoked as one of the most relevant mechanisms that shape the evolution of galaxies. Our goal is to understand the interplay between AGN feedback and the interstellar medium in M 51, a nearby spiral galaxy with a modest AGN and a kpc-scale radio jet expanding through the disc of the galaxy. For this purpose, we combine molecular gas observations in the CO(1−0) and HCN(1−0) lines from the Plateau de Bure interferometer with archival radio, X-ray, and optical data. We show that there is a significant scarcity of CO emission in the ionisation cone, while molecular gas emission tends to accumulate towards the edges of the cone. The distribution and kinematics of CO and HCN line emission reveal AGN feedback effects out to r ~ 500 pc, covering the whole extent of the radio jet, with complex kinematics in the molecular gas which displays strong local variations. We propose that this is the result of the almost coplanar jet pushing on molecular gas in different directions as it expands; the effects are more pronounced in HCN than in CO emission, probably as the result of radiative shocks. Following previous interpretation of the redshifted molecular line in the central 5′′ as caused by a molecular outflow, we estimate the outflow rates to be ṀH2 ~ 0.9 M⊙/ yr and Ṁdense ~ 0.6 M⊙/ yr, which are comparable to the molecular inflow rates (~1 M⊙/ yr); gas inflow and AGN feedback could be mutually regulated processes. The agreement with findings in other nearby radio galaxies suggests that this is not an isolated case, and is probably the paradigm of AGN feedback through radio jets, at least for galaxies hosting low-luminosity active nuclei.